Hearing their Cries: A Talanoa Response - Kolia, Brian Fiu (Biblical interpretation, 2023)
This essay is a response to the stimulating contributions to this volume, by way of hearing. Here, I use the Indigenous Pasifika form of interrogation known as talanoa that allows us to hear and enter into the subconcious state, to perceive the world of animals from these alternative perspectives, which seek to liberate animal voices and push back at colonial systems that are guilty of meddling with our reading and theorizing of the animal-Other. This talanoa allows us to imagine the contributors sitting around a kava bowl in conversation, as we hear them tell their stories, and hear the humour, the pain, the honesty in the animal experiences.